Engineered extracellular vesicles encapsulated Bryostatin-1 as therapy for neuroinflammation. Issue 6 (28th January 2022) - Wu, Wen-Cheng; Tian, Jing; Xiao, Dan; Guo, Yu-Xin; Xiao, Yun; Wu, Xiao-Yu; Casella, Giacomo; Rasouli, Javad; Yan, Ya-Ping; Rostami, Abdolmohamad; Wang, Li-Bin; Zhang, Yuan; et al.
Abstract : Targeted and effective drug delivery to CNS lesion enhanced remyelination in demyelinating disease. Abstract : Targeted and effective drug delivery to central nervous system (CNS) lesions is a major challenge in the treatment of multiple sclerosis (MS). Extracellular vesicles (EVs) have great promise as a drug delivery nanosystem given their unique characteristics, including a strong cargo-loading capacity, low immunogenicity, high biocompatibility, inherent stability, high delivery efficiency, ease of manipulation, and blood–brain barrier (BBB) penetration. Clinical applications are, however, limited by their insufficient targeting capability and "dilution effects" upon systemic administration. Neural stem cells (NSCs) provide an abundant source of EVs because of their remarkable capacity for self-renewal. Here, we developed a novel therapeutic strategy for local delivery and treatment using EVPs, which are derived from NSCs with the expression of the CNS lesion targeting ligand-PDGFRα. Furthermore, we used EVPs as a targeting carrier for encapsulating Bryostatin-1 (Bryo-1), a natural compound with remarkable anti-inflammation ability. Our data showed that Bryo-1 delivered by EVPs was more stable and concentrated in the CNS than native Bryo-1. Systemic injection of a low dosage (1 × 10 8 particles) of EVPs + Bryo-1, versus only EVPs or Bryo-1 administration, significantly ameliorated clinical disease development, decreased the infiltration of pro-inflammatory cells, blocked myelin loss and astrogliosis, protected BBB integrity, and altered microglia pro-inflammatory phenotype in the CNS of EAE mice. Taken as a whole, our study showed that engineered EVs have a CNS targeting capacity, and it provides potentially powerful therapeutic effects for the treatment of various neuroinflammatory diseases.